2008
DOI: 10.1093/annonc/mdm495
|View full text |Cite
|
Sign up to set email alerts
|

Nadir CA-125 concentration in the normal range as an independent prognostic factor for optimally treated advanced epithelial ovarian cancer

Abstract: The CA-125 nadir value is a strong independent prognostic factor for optimally treated adEOC after achieving a complete response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 23 publications
6
41
0
Order By: Relevance
“…13 More recently, different nadir values and trends of elevated CA-125 values within the normal range have been shown to be prognostic of recurrence and survival in patients with ovarian cancer. [14][15][16][17][18] The objective of our study was to evaluate the clinical significance of rising CA-125 levels within the normal range (35 U/mL) in patients with UPSC.…”
Section: Introductionmentioning
confidence: 99%
“…13 More recently, different nadir values and trends of elevated CA-125 values within the normal range have been shown to be prognostic of recurrence and survival in patients with ovarian cancer. [14][15][16][17][18] The objective of our study was to evaluate the clinical significance of rising CA-125 levels within the normal range (35 U/mL) in patients with UPSC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers have been investigating the role of maintenance or consolidation chemotherapy in patients who achieved complete remission (CR) [4,5]. Recently, it has been suggested that nadir serum CA-125 levels 10 U/ml are independently associated with progression free survival (PFS) in the patients with CR after first line therapy [6][7][8][9][10]. Based on these results, the researchers suggested the possibility of using the nadir CA-125 to define the population who may benefit from maintenance chemotherapy [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicate that serum Ca125 level nadir after chemotherapy completion may be a strong prognostic factor for progression free survival time as well as for OS [11,12,13] . It has been showed that women with nadir serum Ca125 lower than 10 U/mL live longer than women with higher nadir [14] . Ca125 regression after two cycles of neoadjuvant chemotherapy appears to be an important prognostic factor for probability of radical surgery and OS for OC patients [15] .…”
Section: Discussionmentioning
confidence: 99%